Himalayan Giant Honey Bee, Cliff Honey Bee (suggested common names) Apis laboriosa Smith (Insecta: Hymenoptera: Apidae) - Michelle Gregory; Cameron Jack (EDIS)
The Featured Creatures collection provides in-depth profiles of insects, nematodes, arachnids and other organisms relevant to Florida. These profiles are intended for the use of interested laypersons with some knowledge of biology as well as academic audiences.